PENINGKATAN KOMPETENSI MAHASISWA: EFEKTIVITAS PROGRAM MAGANG PROFESI PROGRAM STUDI KOMUNIKASI DAN PENYIARAN ISLAM - Hasyim, Nanang Mizwar (UIN Sunan Kalijaga, 2023)
programme designed to shape students' cognitive, affective and psychomotor skills. Knowledge, professional attitude and responsibility can be nurtured through the routine of internship activities. Through assigned activities, students will adapt to professional routines in the professional world. Through the skinative research method using the effectiveness of objectives approach, this research tries to explore whether the professional internship programme that has been carried out by the KPI study programme in improving its competence has been effective. From the results of the research, it was found that the professional internship programme can be said to be effective. This can be seen from the results of good output and outcome achievements. Even so, the implementation still leaves problems. When viewed from the perspective of the management process, it still needs improvement in the implementation process which still depends on the role of the executive committee. As a result, there is a lack of smoothness in other stages of the management process. Namely the stages of supervision and control.